Crystal Structure of Flagellar Export Chaperone FliS in Complex With Flagellin and HP1076 of Helicobacter pylori - Lam, Wendy Wai-Ling; Sun, Kailei; Zhang, Huawei; Au, Shannon Wing-Ngor (Frontiers in Microbiology, 2020)
Functional flagella formation is a widespread virulence factor that plays a critical role in survival and host colonization. Flagellar synthesis is a complex and highly coordinated process. The assembly of the axial structure beyond the cell membrane is mediated by export chaperone proteins that transport their cognate substrates to the export gate complex. The export chaperone FliS interacts with flagellin, the basic component used to construct the filament. Unlike enterobacteria, the gastric pathogen Helicobacter pylori produces two different flagellins, FlaA and FlaB, which exhibit distinct spatial localization patterns in the filament. Previously, we demonstrated a molecular interaction between FliS and an uncharacterized protein, HP1076, in H. pylori. Here, we present the crystal structure of FliS in complex with both the C-terminal D0 domain of FlaB and HP1076. Although this ternary complex reveals that FliS interacts with flagellin using a conserved binding mode demonstrated previously in Aquifex aeolicus, Bacillus subtilis and Salmonella enterica serovar Typhimurium, the helical conformation of FlaB in this complex was different. Moreover, HP1076 and the D1 domain of flagellin share structural similarity and interact with the same binding interface on FliS. This observation was further validated through competitive pull-down assays and kinetic binding analyses. Interestingly, we did not observe any detrimental flagellation or motility phenotypes in an hp1076-null strain. Our localization studies suggest that HP1076 is a membrane-associated protein with a cellular localization independent of FliS. As HP1076 is uniquely expressed in H. pylori and related species, we propose that this protein may contribute to the divergence of the flagellar system, although its relationship with FliS remains incompletely elucidated.